Power of Judges in Deciding Legal Liability of Criminals with Mental Disorders - Irma Sandra; Benny Irawan; M Noor Fajar Al Arif F (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
Murder is one of the substantive crimes whose formulation focuses on prohibited laws and punishable consequences. The aims of this study are 1) to analyze legal responsibility for perpetrators of mental disorders based on positive law in Indonesia; and 2) Analyze the judge's decision considerations for criminal offenders with mental disorders. This research uses normative legal methods with a case approach. This study found that 1) criminal responsibility for perpetrators of criminal acts who experienced psychiatric disorders before being declared mentally ill by expert witnesses, the judicial process continued as it should; 2) The judge considers that the settlement of criminal offenders who experience mental problems depends on the cases referred to in Article 184 paragraph (1) of the Criminal Procedure Code. In conclusion, Article 44 paragraph (1) of the Criminal Code explains what is meant by responsibility, which affects a person's actions before being found to be irresponsible because of a mental disorder, whether all of his actions will be declared completely innocent by law or whether some of his actions are legal. Proof in a criminal trial must also consider the required evidence of at least 2 (two) valid pieces of evidence and the judge has the right to provide a response that the defendant is guilty of committing a crime according to Article 183 of the Criminal Procedure Code.